If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(k + -3) + -6 = 4k + -1(3k + -2) Reorder the terms: 5(-3 + k) + -6 = 4k + -1(3k + -2) (-3 * 5 + k * 5) + -6 = 4k + -1(3k + -2) (-15 + 5k) + -6 = 4k + -1(3k + -2) Reorder the terms: -15 + -6 + 5k = 4k + -1(3k + -2) Combine like terms: -15 + -6 = -21 -21 + 5k = 4k + -1(3k + -2) Reorder the terms: -21 + 5k = 4k + -1(-2 + 3k) -21 + 5k = 4k + (-2 * -1 + 3k * -1) -21 + 5k = 4k + (2 + -3k) Reorder the terms: -21 + 5k = 2 + 4k + -3k Combine like terms: 4k + -3k = 1k -21 + 5k = 2 + 1k Solving -21 + 5k = 2 + 1k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. -21 + 5k + -1k = 2 + 1k + -1k Combine like terms: 5k + -1k = 4k -21 + 4k = 2 + 1k + -1k Combine like terms: 1k + -1k = 0 -21 + 4k = 2 + 0 -21 + 4k = 2 Add '21' to each side of the equation. -21 + 21 + 4k = 2 + 21 Combine like terms: -21 + 21 = 0 0 + 4k = 2 + 21 4k = 2 + 21 Combine like terms: 2 + 21 = 23 4k = 23 Divide each side by '4'. k = 5.75 Simplifying k = 5.75
| 6w-13w-18=-81 | | 10-3(m-2)=7 | | 4x-13=2(3-x) | | 5w+27+4w=9 | | 8-2t=14+t | | 2(2y-1)+y=5(y+3) | | -9x+5(-3x-4)=-42-2x | | 40+40*0+1= | | 2x+7(3x-4)=-2-3x | | -8x^2+24x-18= | | -16+x=450 | | 5x^2+50x=0 | | -5x+x=-16 | | 120x^2-272x+120=0 | | 5*5*5*5= | | 2t^2+2t=3 | | 10-3(-8-2)= | | 120x^2-272x+102=0 | | 10x-0.375-4x=6x | | 2+x=16-6x | | 30a=2a-8 | | 976x-x^2=213.495 | | 1/14=27/7*1/30 | | 10x-2y=5 | | -2x^2+17x-8=0 | | 6x-2y=1 | | -99=33y | | 8j-4k=4 | | 5(k-2)-6=5k-(4k-3) | | 3j+4k=23.5 | | 11f+10g=25 | | Y=150x+800 |